Universal.D: proposta de ferramenta de apoio ao projeto arquitetônico sob a abordagem do Desenho Universal - Maciel, Cyro Visgueiro (2019)
One of the ways to promote accessibility and improve the quality of life of people with permanent or temporary disabilities is Universal Design, which has in its principles, guidelines for design. The research aimed to develop an architectural design support tool, to assist decision making in different design phases in terms of Universal Design principles. Assuming that accessibility laws in Brazil require minimum conditions for this, the contents of NBR 9050:2015, the main Brazilian accessibility standard in buildings, were analyzed, classified and grouped. This analysis allowed the construction of the Universal.D tool, which brings in its contents guidelines for architectural design, as well as the possibility of design analysis at any stage of development, under the Universal Design approach. The tool was tested with fifteen undergraduate and graduate students in Architecture and Urbanism, from the Federal University of Paraíba, and occurred from February to July 2019. The tests for tool construction took place in four moments: first, questionnaires were used to identify gaps in content and graphical interface; the second moment, a focus group was carried out to analyze the elements that make up the tool - content, illustrations and instructions for use in the graphical interface. The third, analyzed the design orientations of the tool through simulation of design situations; The last moment analyzed the design verifications and results presented by the tool. These tests enabled the refinement of the tool, that was approved by the students. Universal.D has proven to be a promising and efficient tool for designer awareness, whether it is in architectural design development, evaluation of ongoing and completed designs, or even the analysis of existing buildings. The main highlights reported by study participants were the simple language and the focus on building users brought by the tool. It is noticeable that there are still adjustments to be made for the effective validation of the tool, such as expanding the sampling of tests for professionals in architectural practice, and the migration to web platforms and applications, to extend the reach of the tool. Finally, the importance of further studies on Universal Design is emphasized to produce knowledge and tools for use by designers.